USER PERCEPTIONS OF PERFORMANCE ACCOUNTING INFORMATION SYSTEM IN THE FACULTY OF ENGINEERING UNIVERSITY GADJAH MADA - Hudalaili, Nikmatul; Isafaatun, SE., MM, Eliya (Accounting, 2009)
Universitas Gadjah Mada (UGM) before defined as a State Owned Legal Entity (BHMN) is a unit under the Ministry of National Education and the status of State Universities. As a government agency, the recording and reporting follow procedures established by the Minister of Finance is using a single entry system. Single entry system does not allow continuous recording for each end of the budget remaining to be deposited back into the State Treasury. These conditions can not produce financial statements in the form of balance sheet, which presents all the assets and liabilities and net assets of UGM in the final period. Determination of the University of Gadjah Mada University as BHMN require periodic financial reports consisting of: Balance Sheet, Statement of Cash Flows, and Statement of Changes in Net Assets. This encouraged management to arrange GMU new accounting system as a tool to generate periodic financial reports. Financial reports should be collected approximately 380 UGM management unit at the UGM. Learning from complexity and the slow flow of information necessary for presentation of financial statements, management GMU decided to use computer applications in recording all financial activity of UGM. The factors that significantly affect user satisfaction to the performance of the SIA include: information content, level of accuracy, display output, benefits, ease of use, timeliness and speed of processing. keywords : performance, accounting information system